Exploring the correlation of patent ownership and firm success: Cases from the LCD flat panel display industry - Ervilia Reul; Frank Tietze; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2007)
The rapid progress of electronic technology in recent decades has led to an increased technical complexity and wide functionality of many products. As a result man-machine interfaces, such as displays became more and more important, wherefore investments and technical progress in these technologies have been enormous since the early 1980s. Nowadays, the demand for small to large size, light weight (flat panel), high resolution, bright, contrast and real colour displays is very strong. This paper emphasizes on patenting and success in the flat panel display (FPD) industry, which had experienced an extraordinary growth in the last decades. The paper focuses on the liquid crystal display technology (LCD) and in particular on the thin film transistor (TFT LCD) sub-technology, since the study indicates that from various FPD technologies, LCD and its sub-technology TFT is the most improved, commercially important and widely used technology for small to large display applications. The aim of the study is to explore the relationship between annual patent applications of eight leading manufacturers and the success in the market of these companies, with the success measured in terms of sales revenues. The results of the study indicate that companies who aggressively patent are the most successful companies in terms of sales revenues and vice versa. A correlation analysis proves that the relation is strongest for a time lag between annual patent applications and subsequent sales revenues of one to two years, thus the optoelectronics could be considered to be a fast cycle-time industry. These findings are in clear contrast to evidence from prior studies, that prove the importance of patents only in particular industries, and especially in long-cycle time industries such as pharmaceuticals.
urn:nbn:de:gbv:830-opus-3324
Keywords: 650; Patents; Database; Market analysis; revenues; sales